2019
DOI: 10.5539/ijbm.v14n9p47
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management Implementation and Firm Performance: Evidence from the Malaysian Oil and Gas Industry

Abstract: This paper intends to vindicate the influence of Enterprise Risk Management (ERM) implementation on firm performance. A sample of 11 oil and gas Public Listed Companies (PLC’s) were selected in this study. Data were collected using content analysis with regard to the companies’ ERM practices and their financial performances. ERM implementation was measured using COSO’s ERM integrated framework while the firm financial performance was assessed through return on assets (ROA) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…The financial industry has opted for ERM practices for the reduction of costs, risk and potential loss (Adam et al 2021;Mustafa and Al-Nimer 2018). Several studies have found that the ERM has a significant effect on the financial performance of companies (Shad and Lai 2019;Liem 2018;Olayinka et al 2017;Soliman and Adam 2017). Another approach has focused on operational performance and ERM (Altanashat et al 2019;Callahan and Soileau 2017;Panić et al 2019).…”
Section: Erm and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The financial industry has opted for ERM practices for the reduction of costs, risk and potential loss (Adam et al 2021;Mustafa and Al-Nimer 2018). Several studies have found that the ERM has a significant effect on the financial performance of companies (Shad and Lai 2019;Liem 2018;Olayinka et al 2017;Soliman and Adam 2017). Another approach has focused on operational performance and ERM (Altanashat et al 2019;Callahan and Soileau 2017;Panić et al 2019).…”
Section: Erm and Firm Performancementioning
confidence: 99%
“…Liem (2018) showed that ERM has a positive and significant influence on banks' profitability, which will be a useful indicator for the shareholders. A recent study by Kashif Shad and Lai (2019) revealed that four components, i.e., supportive internal environment, objective setting, control and monitoring activities of the ERM framework have a significant and positive effect on a firm's performance. Recently, Malik et al (2020) demonstrated that the ERM significantly affects an organization's performance.…”
Section: Erm and Firm Performancementioning
confidence: 99%
“…In literature, green innovation is often used interchangeably for ecological innovation, sustainable innovation, environmental innovation and eco-innovation (Schiederig et al , 2012). In all industrial sectors, green innovation improves the processes and operations that adhere to the ecological design of products and reduce the negative impact on environment (Kashif Shad and Lai, 2019). To achieve the goal of green development, green innovation entails developing new products and processes that can improve the value for consumers and enterprises while reducing negative environmental impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, CSR plays an important role in assisting businesses to comply with government environmental regulations by adopting eco-friendly approaches. This in turn helps them to develop green products, reduce pollution during production processes and implement clean energy production processes (Kashif Shad et al ., 2018). Second, end users/customers are another crucial stakeholder of enterprises that seek to offer green and environmentally friendly products.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…(Dias & McKee, 2010) agents will not provide quality service to their targeted customers without ongoing, on-site supervision and in-store training facilities, to ensure that the agents are sufficiently liquid, always branded, and following the prescribed business processes. For this kinds of business operations banks needs proactive rather than reactive which will incerase the firm financial value, further minimize the risk (Akhtar, Khan, & Khan, 2020;Ali, Johl, & Excellence, 2021;Jan et al, 2021;Johl & Toha, 2021;Shad, Lai, & Management, 2019;Shad & Lai, 2015). (Andrieş, 2009) the character of financial mediators may be explained in principle by the existence of a few unique variables.…”
Section: Literature Reviewmentioning
confidence: 99%